2013
DOI: 10.1016/j.bbalip.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage heterogeneity and cholesterol homeostasis: Classically-activated macrophages are associated with reduced cholesterol accumulation following treatment with oxidized LDL

Abstract: Macrophages are centrally involved during atherosclerosis development and are the predominant cell type that accumulates cholesterol in the plaque. Macrophages however, are heterogeneous in nature reflecting a variety of microenvironments and different phenotypes may be more prone to contribute towards atherosclerosis progression. Using primary human monocyte-derived macrophages, we sought to evaluate one aspect of atherogenic potential of different macrophage phenotypes by determining their propensity to asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…It has been shown that M1 activated macrophages demonstrate reduced foam cell formation in response to oxLDL 36, 87 and that Mox activated macrophages have attenuated phagocytosis and efferocytosis 39 . It would thus have been reasonable to speculate that IGF1R deficiency, which enhances the proinflammatory phenotype as well as Mox marker expression levels, could lead to reduced foam cell formation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that M1 activated macrophages demonstrate reduced foam cell formation in response to oxLDL 36, 87 and that Mox activated macrophages have attenuated phagocytosis and efferocytosis 39 . It would thus have been reasonable to speculate that IGF1R deficiency, which enhances the proinflammatory phenotype as well as Mox marker expression levels, could lead to reduced foam cell formation.…”
Section: Discussionmentioning
confidence: 99%
“…This combined treatment of IFN-γ and TNF-α in mRNA reduced the CD36 expression on macrophages. 33 Recent studies indicate that human neutrophil peptides (HNPs) take part in atherosclerosis development. 34,35 Quinn et al 36 suggest that the HNP induces increase of CD36 expression in the surface of macrophages and as a result contributes to the increased amount of foam cell formation.…”
mentioning
confidence: 99%
“…In particular, participation of focal adhesion kinases and Rho GEFs, which signals CD36 to perform degradation, active migration internalization and binding regulation (Prieto et al, 1994). CD36 can be reduced considerably with treatment by tumor necrosis factor α (TNF-α) and interferon γ combined (Chu et al, 2013). FAK activates actin polymerization and is thought to have an impact on macrophage aggregation and foam cell formation in the arterial intima (Park et al, 2009).…”
Section: Signaling Of Cd36mentioning
confidence: 99%